Quinolinophenothiazine as an electron rich fragment for high efficiency RGB single-layer phosphorescent organic light-emitting diodes. (12th October 2021) - Lucas, Fabien; Tondelier, Denis; Geffroy, Bernard; Heiser, Thomas; Ibraikulov, Olzhas A.; Quinton, Cassandre; Brouillac, Clément; Leclerc, Nicolas; Rault-Berthelot, Joëlle; Poriel, Cyril
Abstract : We report a high efficiency host material constructed on a quinolinophenothiazine core for RGB single-layer phosphorescent organic light emitting diodes. Abstract : The quinolinophenothiazine (QPTZ) fragment is a phenylacridine bridged by a sulphur atom. Despite the appealing properties induced by this bridging ( e.g. strong electron rich character), this fragment has remained almost unexplored to date in organic electronics. Based on this QPTZ fragment, we report herein a high efficiency host for the new generation of the simplified so-called Single-Layer Phosphorescent Organic Light-Emitting Diodes (SL-PhOLEDs). This host material is constructed via the association of an electron rich fragment (QPTZ), and an electron-deficient fragment (2, 7-bis(diphenylphosphineoxide)-fluorene). This molecule displays all the necessary properties to be used in universal SL-PhOLEDs. Red, green and blue SL-PhOLEDs were successfully fabricated and yielded an average external quantum efficiency of ca. 10%. High luminances of ca. 10 000 cd m −2 for red and blue devices and 40 000 cd m −2 for green devices were obtained. These luminances are higher than the best reported to date using structurally related analogues and highlight the strong interest of the QPTZ fragment in such devices. Thanks to its high HOMO level, the QPTZ unit also allows decreasing the threshold voltage, which is a key characteristic in the OLED technology. This work shows the potential of the QPTZ fragment in the design of host materials for high performance SL-PhOLEDs.